PERTIMBANGAN ETIS, DAN KOMPONEN PERILAKU TERENCANA TERHADAP INTENSI WHISTLEBLOWING INTERNAL - Purwantini, Anissa Hakim (EQUILIBRIUM, 2016)
This study empirically examine the influence of professional commitment, ethical judgements, and the components of planned behavior to the intention of internal whistleblowing. The data in this study are primary data which obtained by distributing questionnaires directly to the respondents, undergraduated accounting students at the University of Muhammadiyah. The sampling technique using purposive sampling method. Hypothesis testing is done by multiple regression analysis. The results showed that the only variable subjective norms has positive effects on internal whistleblowing intentions, while the other variables are professional commitment, ethical judgements, attitudes, and perceived behavior control is not having an effect to the intention of internal whistleblowing. Results of regression estimates indicate the predictive ability of the model by 39.2% while the remaining 60.8% is influenced by other factors outside the research model.